Lateral vocalization in Brazilian Portuguese - Howson, Phil J. (2022)
Lateral vocalization is a cross-linguistically common phenomenon where a lateral is realized as a glide, such as [w, j], or a vowel [u, i]. In this paper, we focus on the articulatory triggers that could cause lateral vocalization. We examined Brazilian Portuguese, a language known for the process of lateral vocalization in coda position. We examined the lateral in onset and coda position in four vocalic environments and compared the dynamic tongue contours and contours at the point of maximum constriction in each environment. We also performed biomechanical simulations of lateral articulation and the vocalized lateral. The results indicate increased tongue body retraction in coda position, which is accompanied by tongue body raising. Simulations further revealed that vocalized laterals mainly recruit intrinsic lingual muscles along with the styloglossus. Taken together, the data suggest that vocalization is a result of positional phonetic effects including lenition and additional retraction in the coda position.